2002
DOI: 10.1021/jf0114031
|View full text |Cite
|
Sign up to set email alerts
|

Maillard Reaction of d-Glucose:  Identification of a Colored Product with Conjugated Pyrrole and Furanone Rings

Abstract: Formation of colored compounds during the Maillard reaction of D-glucose with butylammonium acetate in aqueous solution has been investigated. Butylamine was used as a model compound analogous to the lysine side chains of proteins. The previously unknown, yellow product, 4-hydroxy-5-methyl-2-(N-butyl-3-hydroxy-5-(2-hydroxyethyl)pyrrolyl-2-methylidene)-2H-furan-3-one (1a), was isolated from the reaction mixtures and identified by spectroscopic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Our colorimetric results showed that the pentose sugar ribose produced faster rates of change in color parameters and the highest yield of HMW‐MRPs compared to both aldo‐ and ketohexose sugars. Similar findings have been reported in other studies that tested a number of different Maillard reactants 24. In many of these studies, an absorbance reading at 420 nm was used to monitor the formation of late‐stage MRPs,4,25 which include the presence of furans, pyrroles, pyridine, and pyrazine components 2,24.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Our colorimetric results showed that the pentose sugar ribose produced faster rates of change in color parameters and the highest yield of HMW‐MRPs compared to both aldo‐ and ketohexose sugars. Similar findings have been reported in other studies that tested a number of different Maillard reactants 24. In many of these studies, an absorbance reading at 420 nm was used to monitor the formation of late‐stage MRPs,4,25 which include the presence of furans, pyrroles, pyridine, and pyrazine components 2,24.…”
Section: Discussionsupporting
confidence: 62%
“…Similar findings have been reported in other studies that tested a number of different Maillard reactants. 24 In many of these studies, an absorbance reading at 420 nm was used to monitor the formation of late-stage MRPs, 4,25 which include the presence of furans, pyrroles, pyridine, and pyrazine components. 2,24 The change in fluorescence noted herein was attributed to the generation of initial MR products, with a variety of fluorogens being precursors for brown pigments that were subsequently generated, as evidenced by the 420-nm absorbance reading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 b and Table 1 ). This could be explained by putative unintended by-product formation and accumulation due to the Maillard reaction (Lerche et al 2002 ), which was inhibiting growth of D. amlyolyticus . According to a study on anaerobic bacteria, melanoidins, the product of the Maillard reaction, have strong prebiotic potential and can be used as carbon source by particularly Bifidobacterium spp.…”
Section: Resultsmentioning
confidence: 99%